2004
DOI: 10.1530/eje.0.1500225
|View full text |Cite
|
Sign up to set email alerts
|

The role of CXCR5 and its ligand CXCL13 in the compartmentalization of lymphocytes in thyroids affected by autoimmune thyroid diseases

Abstract: Objective: Graves' disease (GD) and Hashimoto's thyroiditis (HT) are characterized by lymphocytic infiltrates partly resembling secondary lymphoid follicles in the thyroid. CXCR5 and its ligand CXCL13 regulate compartmentalization of B-and T-cells in secondary lymphoid organs. The aim of the study was to elucidate the role of this chemokine receptor -ligand pair in thyroid autoimmunity. Methods: Peripheral blood and thyroid-derived lymphocyte subpopulations were examined by flow cytometry for CXCR5. CXCR5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 41 publications
(36 reference statements)
2
49
0
Order By: Relevance
“…Moreover, tertiary lymphoid organs also frequently appear in autoimmune diseases such as Sjo¨gren's syndrome (Hjelmervik et al, 2005), chronic obstructive pulmonary disease, rheumatoid arthritis (RA) (Young et al, 1984;Takemura et al, 2001), Graves' disease (Armengol et al, 2003;Aust et al, 2004) or multiple sclerosis (Prineas 1979;Serafini et al, 2004). In most of these diseases, elevated expression of LT or its target genes has been detected, supporting LT's role in lymphoid neogenesis (Drayton et al, 2006).…”
Section: Lt and Inflammationmentioning
confidence: 99%
“…Moreover, tertiary lymphoid organs also frequently appear in autoimmune diseases such as Sjo¨gren's syndrome (Hjelmervik et al, 2005), chronic obstructive pulmonary disease, rheumatoid arthritis (RA) (Young et al, 1984;Takemura et al, 2001), Graves' disease (Armengol et al, 2003;Aust et al, 2004) or multiple sclerosis (Prineas 1979;Serafini et al, 2004). In most of these diseases, elevated expression of LT or its target genes has been detected, supporting LT's role in lymphoid neogenesis (Drayton et al, 2006).…”
Section: Lt and Inflammationmentioning
confidence: 99%
“…Lymphoid-like microstructures have been reported in some autoimmune conditions (15)(16)(17)(18). If such structures are true extranodal lymphoid tissues, then they would express the same molecular effectors as normal secondary lymphoid organs and display similar tissue architecture (12,13,(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…These organized aggregates of lymphocytes are induced by inflammation, unlike those in developmentally programmed secondary lymphoid organs (spleen and lymph nodes) which they resemble. Previous studies have indicated that secondary and tertiary lymphoid structures share many commonalities, such as their organization and underlying chemotactic factors (11)(12)(13). Some tertiary lymphoid aggregates have also been shown to contain germinal centers (GC; Refs.…”
mentioning
confidence: 99%